Non-self-sustained arc discharge in vapors of constructional materials of nuclear power engineering - Borisenko, A.G.; Kostin, E.G.; Rokytskyi, O.А.; Fedorovich, O.A. (Вопросы атомной науки и техники, 2018)
The paper presents the results of experimental studies of the conditions of ignition and burning for non-selfsustained arc discharges in nickel and tantalum vapors. The investigations were carried out with the aim of
developing new methods for efficient generation of plasma-free and highly ionized plasma flows of structural
materials of nuclear power engineering. In the experiments, the minimum power required to obtaining a sufficient
vapor pressure of working material and ignition of vacuum arc discharges was obtained. The values of the minimum
discharge power in the conditions of their stable burning were also determined; the current-voltage characteristics of
the discharges in vacuum and under conditions of gas input into the vacuum chamber were studied. It is shown that
the created plasma streams can be used to deposit the films not only on metallic and semiconductor materials, but
also on dielectric substrates. Представлено результати експериментальних досліджень умов запалювання і горіння несамостійних
дугових розрядів у парах нікелю та танталу. Дослідження були виконані з метою розробки нових методів
ефективної генерації безкрапельних і високоіонізованих потоків плазми конструкційних металів ядерної
енергетики. В експериментах були визначені мінімальні потужності, необхідні для одержання тиску парів
робочого матеріалу, достатнього для запалювання і розвитку вакуумних дугових розрядів у парах металів.
Були також визначені величини мінімальної потужності розрядів за умови їх стабільного горіння, вивчені
вольт-амперні характеристики розрядів у вакуумі та в умовах напуску газу до розрядної камери. Показано,
що утворювані плазмові потоки можуть бути використані для осадження плівок не лише на металеві та
напівпровідникові, але й на діелектричні підкладинки. Представлены результаты экспериментальных исследований условий зажигания и горения
несамостоятельных дуговых разрядов в парах никеля и тантала. Исследования были проведены с целью
разработки новых методов эффективной генерации бескапельных и высокоионизированных потоков плазмы
конструкционных материалов ядерной энергетики. В экспериментах были определены минимальные
мощности, необходимые для получения достаточного для развития разрядов давления паров рабочего
материала и зажигания вакуумных дуговых разрядов. Были также определены величины минимальной
мощности разрядов в условиях их стабильного горения, изучены вольт-амперные характеристики разрядов в
вакууме и в условиях напуска газа в разрядную камеру. Показано, что создаваемые плазменные потоки
могут быть использованы для осаждения пленок не только на металлические и полупроводниковые, но и на
диэлектрические подложки.